Penanganan Gangguan Penyalahgunaan Zat di Panti Rehabilitasi LRPPN Medan - Zega, Putri Juniman; Triana, Angelique; Fahriza, Tasya; Ritonga, Fajar Utama; Abdurahman, Eka Prahadian (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2024)
Field observation is a data collection method that involves direct observation of phenomena or situations at specific locations. This method includes recording behaviors, patterns, or characteristics observed directly on-site, both in everyday contexts and formal settings such as scientific or situational research. This study was conducted at the LRPPN Rehabilitation Center in the Helvetia area, a facility for the rehabilitation of individuals using narcotics. Various methods are employed in this rehabilitation process to prevent clients from returning to the consumption of illicit substances. The approaches applied are tailored to the conditions of each client, aiming to encourage openness and meet individual needs. This study emphasizes the importance of attention and support in providing effective methods for clients with mental health disorders, as well as the significance of active involvement within their families and environments.